EVALUATION OF STABILITY OF MASONRY MINARET IN HIGH SEISMICITY REGION - Amir Čaušević, Nerman Rustempašić (AR: Arhitektura, Raziskave, 2012)
This paper is a result of authors' involvement in the Project ofRehabilitation of the Ferhad-Pasha’s Mosque.The aim of the project was to construct an authentic buildingusing authentic materials, while respecting the principlesof aesthetics and the approaches of ancient builders. Thebuilding will be reconstructed to the same condition as it wasbefore destruction using similar construction methods. It isforeseen that it will be difficult to comply with this principle,due to significant developments in architecture since the initialconstruction. Monuments are precious things that must berespected, and altered as little as possible. These observationscould lead to contradictory decisions, at times accepting ahigher degree of risk in order to avoid or limit changes to theoriginal concept. The Ferhad-Pasha’s Mosque is the work of ahighly-qualified mimar (builder) and muhendis (engineer), aproduct of Sinan's school.On 7 May 1993 the mosque was dynamited and razed to theground, and the material removed to the city landfill site inRamiće. The computer program SAP 2000 was used to analyzethe minarets with shell elements. Assuming no tension, it wasfound that the stress was exceeded to a greater extent underthe earthquake load. Deformations caused by shear forceshave an insignificant influence upon the rigidity of tall slenderstructures, thus they can be neglected in practical calculations.To reduce the tensile stress, which appears due to seismicmovements, we recommended two solutions.